2022
DOI: 10.3390/diagnostics12030692
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Weighted Imaging in the Assessment of Tumor Grade in Endometrial Cancer Based on Intravoxel Incoherent Motion MRI

Abstract: The aim of this study is to investigate the possibility of predicting histological grade in patients with endometrial cancer on the basis of intravoxel incoherent motion (IVIM)-related histogram analysis parameters. This prospective study included 52 women with endometrial cancer (EC) who underwent MR imaging as initial staging in our hospital, allocated into low-grade (G1 and G2) and high-grade (G3) tumors according to the pathology reports. Regions of interest (ROIs) were drawn on the diffusion weighted imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Important prognostic factors for EC are the histological subtype of tumor, histological grade, stage, the depth of myometrial invasion and the presence of lymphovascular invasion, among which the stage and histological grade correlate with the risk of lymph node metastasis and the patient's prognosis (33)(34)(35). EC with a low histological grade has a lower cell density and greater movement of water molecules in the matrix and therefore tends to have higher ADC values.…”
Section: Discussionmentioning
confidence: 99%
“…Important prognostic factors for EC are the histological subtype of tumor, histological grade, stage, the depth of myometrial invasion and the presence of lymphovascular invasion, among which the stage and histological grade correlate with the risk of lymph node metastasis and the patient's prognosis (33)(34)(35). EC with a low histological grade has a lower cell density and greater movement of water molecules in the matrix and therefore tends to have higher ADC values.…”
Section: Discussionmentioning
confidence: 99%
“…Чувствительность данного признака в дифференциальной диагностике ВЛС от ДЛС составила 87,5 %, специфичность -70 %. Магнитно-резонансная томография (МРТ) в сочетании с методикой диффузионно-взвешенной МРТ (ДВ-МРТ) в настоящее время является одним из наиболее перспективных методов, позволяющим с высокой точностью судить о внутреннем строении опухоли и, по мнению ряда авторов, косвенно оценивать ее морфологическую структуру [17][18][19][20][21][22][23].…”
Section: рефератunclassified
“…Intravoxel incoherent motion includes bi-exponential and stretched-exponential models and is used to reflect capillary microcirculatory perfusion, while DKI describes tissue heterogeneity. The IVIM model was previously found to be related to pathological indicators and useful for the disease grading of EC (Ma et al 2023 ; Satta et al 2021 ; Chryssou et al 2022 ); it also showed higher efficacy than ADC in differentiating an endometrial malignancy from the normal endometrium (Liu et al 2016 ). Diffusion kurtosis imaging is based on the non-Gaussian model and has a high sensitivity for reflecting the complexity of the tissue microstructure (Jensen et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%